Risk and Protective Factors for Sudden Cardiac Death: An Umbrella Review of Meta-Analyses - Tsartsalis, Dimitrios; Korela, Dafni; Karlsson, Lars O.; Foukarakis, Emmanouil; Svensson, Anneli; Anastasakis, Aris; Venetsanos, Dimitrios; Aggeli, Constantina; Tsioufis, Costas; Braunschweig, Frieder; Dragioti, Elena; Charitakis, Emmanouil (Frontiers in Cardiovascular Medicine, 2022)
Background: Sudden cardiac death (SCD) is a global public health issue, accounting for 10-20% of deaths in industrialized countries. Identification of modifiable risk factors may reduce SCD incidence. Methods: This umbrella review systematically evaluates published meta-analyses of observational and randomized controlled trials (RCT) for the association of modifiable risk and protective factors of SCD. Results: Fifty-five meta-analyses were included in the final analysis, of which 31 analyzed observational studies and 24 analyzed RCTs. Five associations of meta-analyses of observational studies presented convincing evidence, including three risk factors (diabetes mellitus (DM), smoking, and early repolarization pattern (ERP)) and two protective factors (implanted cardiac defibrillator (ICD) and physical activity). Meta-analyses of RCTs identified five protective factors with a high level of evidence: ICDs, mineralocorticoid receptor antagonist (MRA), beta-blockers, and sodium-glucose cotransporter-2 (SGLT-2) inhibitors in patients with HF. On the contrary, other established, significant protective agents (i.e. amiodarone and statins along with angiotensin-converting enzyme (ACE) inhibitors in heart failure (HF)), did not show credibility. Likewise, risk factors as left ventricular ejection fraction in HF, and left ventricular hypertrophy, non-sustain ventricular tachycardia, history of syncope or aborted SCD in pediatric patients with hypertrophic cardiomyopathy, presented weak or no evidence. Conclusions: Lifestyle risk factors (physical activity, smoking), comorbidities like DM, and electrocardiographic features like ERP constitute modifiable risk factors of SCD. Alternatively, the use of MRA, beta-blockers, SGLT-2 inhibitors, and ICD in patients with HF are credible protective factors. Further investigation targeted in specific populations will be important for reducing the burden of SCD. Systematic review registration: PROSPERO registry number: CRD42020216363